∵
a1×[a1+a2+a3+a4+a5.+a(n)]
=2×[2×﹙2^n-1﹚÷﹙2-1﹚]
=2²×﹙2^n-1﹚
=2^﹙n+2﹚-2²
a2×[a2+a3+a4+a5...+a(n)]
=2²×【2²×[2^﹙n-1﹚-1]÷﹙2-1﹚】
=2⁴×[2^﹙n-1﹚-1]
=2^﹙n+3﹚-2⁴
a3×[a3+a4+a5...+a(n)]
=2³×【2³×[2^﹙n-2﹚-1]÷﹙2-1﹚】
=2^﹙n+4﹚-2^6
……
a(n-1)×[a(n-1)+a(n)]
=2^﹙n-1﹚×【2^﹙n-1﹚×[2^2-1]÷﹙2-1﹚】
=2^﹙2n﹚-2^﹙2n-2﹚
a(n)×[a(n)+a(n)]
=2^n×【2^n×2】
=2^﹙2n+1﹚
∴T(n)=a1×[a1+a2+a3+a4+a5.+a(n)]+a2×[a2+a3+a4+a5...+a(n)]+a3×[a3+a4+a5...+a(n)]+.a(n-1)×[a(n-1)+a(n)]++a(n)×[a(n)+a(n)]
=2^﹙n+2﹚-2²+2^﹙n+3﹚-2⁴+2^﹙n+4﹚-2^6+……+2^﹙2n﹚-2^﹙2n-2﹚+2^﹙2n+1﹚
=【2^﹙n+2﹚+2^﹙n+3﹚+2^﹙n+4﹚+……+2^﹙2n﹚+2^﹙2n+1﹚】-【2²+2⁴+2^6+……+2^﹙2n-2﹚】
=【2^﹙n+2﹚×﹙2^n-1﹚÷﹙2-1﹚】-【2²×[2^﹙2n-2﹚-1]÷﹙2-1﹚】
=2^﹙2n+2﹚-2^﹙n+2﹚-2^﹙2n﹚+2²